Efektivitas Buku Penghubung sebagai Sarana Komunikasi Guru dan Orang Tua tentang Perkembangan Ibadah Anak - Wulan Sari; Firda Ayu Wahyuni (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
The connecting book becomes an information medium for school activities and children’s worship activities at home. In the connecting book, the teacher communicates condition of the child at school so that communication is established between teacher and parents. This can have a positive impact on the progress of children’s learning and the progress of children’s worship at home. The purpose of this reaserch is (1) To find out the effectiveness of connecting books as a mean of communication between teachers and parents about the development of children’s worship. (2) To find out what obstacles are inhibiting the effect of the connecting book as a means of communication between teachers and parents about the development of children’s worship. This research is a field research approach used ia a descriptive qualitative approach, data collection is carried out by conducting observation, interviews, and documentation. Data analysis techniques in this study are using data collection, data reduction, data presentation and drawing conclusions. To check the validity of the data, researchers used triangulation of sources. Based on the results of this research shows that the use of connecting books as a means of communication between teachers and parents about the development of children’s worship has been very effective, because with this connecting book teacher and parents are very helped in communicating through the connecting book about the development of children’s worship. There are several constraints regarding the effectiveness of connecting books as a means of communication between teachers and parents about the development of children’s worship, among others: 1) parents do not follow up on the teacher’s response regarding the development of children’s worship through the connecting book. 2) parents are less active in responding to information from teachers about the development of children’s worship through connecting books.